Reform and inequality during the transition: An analysis using panel houshold survey data ; 1990 - 2005 - Branko Milanovic; Lire Ersado (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
This paper, using for the first time household survey data from 26 post-communist countries, covering the period 1990-2005, examines correlates of unprecedented increases in inequality registered by most of these economies. We find that, after controlling for country-fixed effects and type of survey used, economic reform (measured by the EBRD index) is strongly negatively associated with bottom deciles' income shares and positively with income shares of the top two deciles. However, once economic reform is broken into its different component parts, the picture is more nuanced: large-scale privatization and infrastructure reform (mostly consisting of privatization and higher fees) are responsible for this pro-inequality effect while small-scale privatization tends to raise income shares of the bottom deciles. Acceleration in growth is also pro-rich. On the other hand, democratization (measured by the Polity measure) is strongly pro-poor, as is lower inflation. Somewhat surprisingly, we find no evidence that higher government spending as share of GDI reduces inequality.
Keywords: D31; P3; 330; inequality; transition; economic policy